Mechanical and ballistic analysis of aramid/vinyl ester composites. (February 2018) - Pagnoncelli, Marlova; Piroli, Vanessa; Romanzini, Daiane; Pereira, Iaci M; Rodrigues Dias, Rafael; Amico, Sandro C; Zattera, Ademir J
This study focused on evaluating mechanical and dynamic-mechanical properties of polyaramid/vinyl ester composites, as a function of the fiber content. Furthermore, split Hopkinson pressure bar technique and V50 Ballistic limit tests were performed. Composites were prepared by resin transfer molding (RTM) with different fiber content, samples being identified as AD4, AD5 and AD6 (with 4, 5 and 6 polyaramid layers, respectively). Initially, fiber, void and matrix contents were calculated and statistically analyzed, in different regions of the composites. Mechanical and dynamical mechanical properties of the composites were improved by using higher fiber content. For example, impact strength of AD6 composite was 35% higher than AD4. Moreover, increase in the fiber content promoted an increase in tenacity and stress of the composites, in the same strain rate. Velocity limit in AD6 sample was estimated in ballistics tests and it was concluded that the composite obtained could accomplish the level I requisites of ballistic protection with V50 of 304 m.s −1 .